Children’s participation in early childhood education: A theoretical overview - Correia, N.; Aguiar, C.; Amaro, F. (Contemporary Issues in Early Childhood, 2023)
Children’s right to participate in all matters and decisions affecting them has gained recognition in society. Its promotion is recommended from an early age – namely, in early childhood education settings – and it is described as benefiting children, adults and the community in general. Given the complex and polysemic meaning of participation, different conceptualizations, models and perspectives have emerged. In this article, the authors provide a theoretical overview, describing relevant models, concepts and contributions from distinct perspectives and fields of knowledge – sociological, educational, developmental and sociocultural – as well as contributions from social policy. This overview is particularly relevant to inform research and practice about children’s participation in early childhood education.